The influence of perceived classroom environment on the learning effectiveness of the association of southeast Asian international students studying in China: The mediating role of learning engagement - Fu, Fuzhen; Xie, Youzhong (Edelweiss Applied Science and Technology, 2024)
This study aims to analyze and comprehend the influence of the classroom environment on the learning effectiveness of the Association of Southeast Asian (ASEAN) students in China especially the significance of learning engagement. Confirmatory factor analysis, descriptive analysis, reliability analysis, correlation analysis and regression analysis were used in this study. 503 useful questionnaires were analyzed through SPSS 22 and AMOS. Both classroom environment cognition and learning engagement could improve ASEAN students' learning effectiveness and learning engagement played a certain mediating effect. The classroom environment and learning engagement are the two primary factors that need to be taken into consideration if ASEAN students in China are to increase their learning efficacy. The more welcoming the classroom environment, the more they can concentrate on participating in various learning activities and the better their learning effectiveness will be. The research object is the ASEAN students in Guangxi Province using the quantitative analysis method of a questionnaire survey. Such as interview methods and other means to further grasp the classroom environment, learning engagement and learning effectiveness of each ASEAN student in China. No studies were conducted on students from ASEAN in other provinces. The cognitive classroom environment can fully affect the learning effectiveness of students from ASEAN countries in China which brings certain theoretical conditions for improving the teaching quality of global students. This study finds out the relationship between classroom environment, learning effectiveness and learning engagement and understands that learning engagement can show a mediating effect which provides certain support for the subsequent in-depth analysis.